2014
DOI: 10.1080/0144929x.2014.942754
|View full text |Cite
|
Sign up to set email alerts
|

Police message diffusion on Twitter: analysing the reach of social media communications

Abstract: Social media are becoming increasingly important for communication between government organisations and citizens. Although research on this issue is expanding, the structure of these new communication patterns is still poorly understood. This study contributes to our understanding of these new communication patterns by developing an explanatory model of message diffusion on social media. Messages from 964 Dutch police force Twitter accounts are analysed using trace data drawn from the Twitter™ API to explain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 48 publications
1
43
2
Order By: Relevance
“…This agrees with a previous study [24] indicating that replies were associated with greater message diffusion. Our results disagree with others indicating that replies address specific users, not the whole Twitter network so that those not involved might be disengaged [25]. User popularity and context of reply may explain the difference between the 2 sides.…”
Section: Discussioncontrasting
confidence: 99%
“…This agrees with a previous study [24] indicating that replies were associated with greater message diffusion. Our results disagree with others indicating that replies address specific users, not the whole Twitter network so that those not involved might be disengaged [25]. User popularity and context of reply may explain the difference between the 2 sides.…”
Section: Discussioncontrasting
confidence: 99%
“…This paper reports analyses of the responses to our electronic survey about social media practices gathered from users of four U.S. police departments' Facebook and Twitter accounts: Billerica, MA; Omaha, NE; Sparks, NV; and Washoe County, NV. Heuristics guiding our selection of these cases included indicators of national reputation as evidenced by social media activity (such as frequency of posts, followers, friends and impressions of posts) along with municipal rankings declaring finalists for the SM Excellence Awards from Connected Cops for 2012, 2013, and 2014 2 ; the 50 Most Social Media Friendly Police Departments in America's Largest Cities 3 ; U.S. Law Enforcement Agencies with the Most Twitter Followers 4 or Facebook "Likes" 5 ; The Best Social Media Cities 6 ; and Top 10 Most Tech-Friendly Cities 7 . Many of these lists include subcategories by police department/city size assisting in the selection of the top performing police departments stratified by population.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of Facebook activities of four metropolitan police departments reveals that they employed different social media management strategies, which caused different patterns of audience engagement [6]. Some types of Twitter messages are more likely to be forwarded and shared by the audience than others [7], and police officers' presentation strategies in Twitter messages can affect the public's perceptions of the police [8].…”
Section: Public Response To Police Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies show that images and videos increase the attention people pay to the content of messages and frames (Bail et al, 2017;Vasi et al, 2015) and contribute to the construction of collective identities (for a review, see Chapter 2 of this dissertation). Furthermore, previous research has found that the use of URLs or hyperlinking, as a way to provide direct access to external online resources, not only increases message diffusion (Velde, Meijer, & Homburg, 2015) and individuals' online influence (Johnson et al, 2015), but is also instrumental in collective action (Jacobson & Mascaro, 2016;Pilny & Shumate, 2012). External linking is quite widespread on Twitter as it allows users to extend their discourse beyond the platform's 140-character tweet length.…”
Section: Control Variablesmentioning
confidence: 99%